Death in the land of Encantos - Diaz, Lav
A Filipino poet named Benjamin Agusan (Roeder Camanag) is the hapless native who returns to his hometown Padang to witness the aftermath of the super typhoon. For the past seven years, Benjamin had been living in an old town called Kaluga in Russia. With his grant and residency, he taught and conducted workshops in a university. The poet published two books of sadness and longing in the process. In Russia, Benjamin was able to shoot video collages, fell in love with a Slavic beauty, buried a son, and almost went mad. He came back to bury his dead-father, mother, sister and a lover. He came back to face Mount Mayon, the raging beauty and muse of his youth. He came home to confront the country that he so loved and hated, the Philippines. He came back to die in the land of his birth. He wanders around the obliterated village meeting old friends and lovers.